2012
DOI: 10.1103/physrevc.86.054609
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic two-nucleon overlaps and knockout reactions from12C

Abstract: The nuclear structure dependence of direct reactions that remove a pair of like or unlike nucleons from a fast 12 C projectile beam are considered. Specifically, we study the differences in the two-nucleon correlations present and the predicted removal cross sections when using p-shell shell-model and multi-hω no-core shell-model (NCSM) descriptions of the two-nucleon overlaps for the transitions to the mass A = 10 projectile residues. The NCSM calculations use modern chiral two-nucleon and three-nucleon (NN +… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…This result contrasts with those reported in Ref. [20] where no correlation between the cross sections and the rms radii of the Nilsson states has been found. In Fig.…”
Section: B Nucleon Knockout From 31 Necontrasting
confidence: 99%
See 3 more Smart Citations
“…This result contrasts with those reported in Ref. [20] where no correlation between the cross sections and the rms radii of the Nilsson states has been found. In Fig.…”
Section: B Nucleon Knockout From 31 Necontrasting
confidence: 99%
“…On the other hand, Ref. [20] (see their Fig. 5) has shown that cross sections have some sensitivity to the relative sizes of the core and neutron wave function.…”
Section: B Nucleon Knockout From 31 Nementioning
confidence: 99%
See 2 more Smart Citations
“…3 We believe that this is preferable to the commonly adopted procedure whereby the theoretical lineshapes are normalised to the peak of the experimental distribution. 4 These may arise from effects not incorporated in the model employed here [41,42], the choice of the model or formalism (see, for example, refs. [43,44]) and uncertainties in the parameters of the model itself.…”
mentioning
confidence: 99%